2017
DOI: 10.1073/pnas.1714963114
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor ISX mediates the cross talk between diet and immunity

Abstract: The intestinal epithelium is a major site for the conversion of dietary β-carotene to retinaldehyde by the enzyme BCO1. The majority of retinaldehyde is further metabolized to retinol (vitamin A), esterified and packaged into triacylglycerol-rich chylomicrons for bodily distribution. Some serve on-site for the synthesis of retinoic acid, a hormone-like compound, which exerts pleiotropic and dominant effects on gastrointestinal immunity. We report here that the intestine-specific homeobox protein ISX is critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…To probe in vivo the contributions of the two CCDs to the metabolism of an asymmetric provitamin A carotenoid, we employed mice lacking the transcription factor ISX ( Isx −/− mice). These mice display significantly higher intestinal carotenoid absorption and conversion rates than wild type (WT) mice (35). As model carotenoids, we used the symmetric BC and the asymmetric CX.…”
Section: Resultsmentioning
confidence: 99%
“…To probe in vivo the contributions of the two CCDs to the metabolism of an asymmetric provitamin A carotenoid, we employed mice lacking the transcription factor ISX ( Isx −/− mice). These mice display significantly higher intestinal carotenoid absorption and conversion rates than wild type (WT) mice (35). As model carotenoids, we used the symmetric BC and the asymmetric CX.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that gastrointestinal immunity is severely impaired in ISX-deficient mice when subjected to BC feeding (42). We now observed that the different diets had a profound effect on gastrointestinal immunity and barrier function in LRAT-deficient mice.…”
Section: Discussionmentioning
confidence: 63%
“…Notably, among the all members of the hypoxia-responsive gene set ( ISX, CLCA4 , SLC5A8, TEX11, CRABP1, CLC12 , and BGN1 ), Intestinal Specific homeobox protein (ISX ) is the prominant factor that is reported to be involved in metabolic activities and disorders in humans. ISX has been reported to regulate the metabolic flux and immune system [38]. This generated an interest to study the relevance and function of ISX in PDAC disease.…”
Section: Resultsmentioning
confidence: 99%